The Importance of the Fluency Test in Neuropsychological Diagnostics - Jovčić, Ivana (Medical Word, 2026)
The study aimed to examine verbal fluency as an indicator of executive functions in a person diagnosed with a schizophrenia spectrum disorder compared to a typically functioning individual. The Verbal fluency test (VFT) is used, which includes phonemic and semantic fluency tasks. The test was conducted on two participants – one with schizophrenia and one control participant from the typical population. The number of words produced within the given time limits was measured, as well as qualitative aspects such as clustering and shifting. Results showed a significant decrease in phonemic fluency in the person with schizophrenia, while semantic fluency was mildly reduced but relatively preserved. Results were within the expected ranges in the participant from the typical population, with clearly expressed verbal flexibility and appropriate control of verbal production. The findings confirm that the VFT can effectively identify differences in executive functions and lexical-semantic system organization between these groups. The test represents a valuable tool in neuropsychological assessment, especially in the context of the schizophrenia spectrum, allowing for differential diagnosis and monitoring of disease progression.
Keywords: executive functions; phonemic fluency; semantic fluenc; schizophrenia; verbal fluency